Selective Arterial Embolization for Palliative Treatment of Intractable Hematuria: Outcomes and Safety in 12 Patients - Allameh, Farzad; Khameneh Bagheri, Arash; Samenezhad, Sina (Archives of Men's Health, 2025)
Introduction: Intractable hematuria due to advanced urological malignancies or radiation cystitis presents a major therapeutic challenge, especially in patients unfit for surgery. Selective arterial embolization (SAE) is a minimally invasive option for achieving hemostasis in such cases. Methods: We retrospectively reviewed 12 patients treated with SAE between 2021 and 2025 for persistent hematuria caused by bladder cancer (n=7), radiation cystitis (n=3), or prostate cancer (n=2). Embolization was performed using super selective catheterization and Embospheres (500–700 µm). Clinical success was defined as significant or complete resolution of hematuria without additional invasive treatment. Results: Clinical success was achieved in 9 (75%) patients and technical success in 10 (83%). Three patients required further interventions, including one cystectomy. No major complications were reported. Most (75%) patients tolerated the procedure well without recurrence. Conclusion: SAE is a safe and effective palliative treatment for refractory hematuria, offering meaningful symptom relief and reducing the need for major surgery in high-risk patients.